PENGARUH KEGIATAN EKONOMI MELALUI SEWA LAHAN TERHADAP PENDAPATAN PETANI PADI DI DESA NANOWA - Fitrianis Laia; Yasozanolo Gaho (Curve Elasticity: Jurnal Pendidikan Ekonomi, 2022)
Soil is one of the factors of production where agricultural products are produced which have a large share in cultivation, because the amount of agricultural production is strongly influenced by the narrow area of ​​land. The purpose of this study was to determine the effect of land rent on the income of rice farmers in Nanowa village. The main population used is a sample of 30 rice farmers and 30 rice farmers. Data collection techniques include questionnaires, interviews (interviews) and documentation. The data analysis technique used is validity test, reliability test, data normality test and simple linear regression test. The results of this study indicate that land rent has a positive and significant effect on the income of farmers in Nanowa village in the range of 57.7%. This means that the larger the area of ​​land leased and managed by farmers, the higher the rental costs and income from farming. Land ownership also indirectly affects the income of farmers in Nanowa Village. Farmers thus have their own land ownership status, so their income level is higher than farmers who rent land from other farmers. What researchers need to reveal is that farmers must focus on agricultural activities to meet their daily needs, and farmers also do other work to supplement their income, such as growing vegetables, corn, chilies and long beans